The grapevine LysM receptor-like kinase VvLYK5-1 recognizes chitin oligomers through its association with VvLYK1-1 - Roudaire, Thibault; Marzari, Tania; Landry, David; Löffelhardt, Birgit; Gust, Andrea A.; Jermakow, Angelica; Dry, Ian; Winckler, Pascale; Héloir, Marie-Claire; Poinssot, Benoit (Frontiers in Plant Science, 2023)
The establishment of defense reactions to protect plants against pathogens requires the recognition of invasion patterns (IPs), mainly detected by plasma membrane-bound pattern recognition receptors (PRRs). Some IPs, also termed elicitors, are used in several biocontrol products that are gradually being developed to reduce the use of chemicals in agriculture. Chitin, the major component of fungal cell walls, as well as its deacetylated derivative, chitosan, are two elicitors known to activate plant defense responses. However, recognition of chitooligosaccharides (COS) in Vitis vinifera is still poorly understood, hampering the improvement and generalization of protection tools for this important crop. In contrast, COS perception in the model plant Arabidopsis thaliana is well described and mainly relies on a tripartite complex formed by the cell surface lysin motif receptor-like kinases (LysM-RLKs) AtLYK1/CERK1, AtLYK4 and AtLYK5, the latter having the strongest affinity for COS. In grapevine, COS perception has for the moment only been demonstrated to rely on two PRRs VvLYK1-1 and VvLYK1-2. Here, we investigated additional players by overexpressing in Arabidopsis the two putative AtLYK5 orthologs from grapevine, VvLYK5-1 and VvLYK5-2. Expression of VvLYK5-1 in the atlyk4/5 double mutant background restored COS sensitivity, such as chitin-induced MAPK activation, defense gene expression, callose deposition and conferred non-host resistance to grapevine downy mildew (Erysiphe necator). Protein-protein interaction studies conducted in planta revealed a chitin oligomer-triggered interaction between VvLYK5-1 and VvLYK1-1. Interestingly, our results also indicate that VvLYK5-1 mediates the perception of chitin but not chitosan oligomers showing a part of its specificity.